DETERMINATION OF SOME HEAVY METALS AND MINERAL NUTRIENTS OF BAY TREE (LAURUS NOBILIS L.) IN BARTIN CITY, TURKEY - (:unkn) unknown (PAKISTAN BOTANICAL SOC, 2012)
Concentrations of Al, Cd, Cu, Ni, and Pb in Laurus nobilis L. were examined for assessment of the impact of heavy metal exposure during winter periods, since these metals have the highest toxic potential. In this study, leaf (washed and unwashed), bark and branch samples of L. nobilis and soil samples were collected from 13 different localities, belonged to three stations. In conjunction with analyzing impact of the heavy metal exposure on the city using L. nobilis as a biomonitoring tool, the uptake and composition of mineral nutrients of L. nobilis were also investigated for determining the effects of heavy metals on mineral nutrition metabolism of the plant. The heavy metal and mineral nutrient concentrations of the collected samples were measured by using ICP-OES. The obtained data was analyzed with SPSS statistics program. As a result of measurements, the lowest and highest heavy metal accumulations and the amount of mineral nutrients measured in plants were as follows; Al (14.69-122.44 mg/kg d. wt), Cd (0.23-0.89 mg/kg d. wt), Cu (1.64-14.25 mg/kg d. wt.), Ni (0.001-0.45 mg/kg d. wt.), Pb (2.06-5.28 mg/kg d. wt.) and B (1.04-6.67 mg/kg d. wt.), Ca (1195.34-4919.03 mg/kg d. wt.), Fe (17.13-203.25 mg/kg d. wt.), K (538.99-3778.37 mg/kg d. wt.), Mg(48.1-268.5 mg/kg d. wt.), Na (24.91-77.43 mg/kg d. wt.) and Zn (4.75-15.74 mg/kg d. wt.). According to the experimental data, the volume of the air pollution was analyzed and found significant in the city. Also, it was noticed that the metabolism of mineral nutrients of L. nobilis was altered by heavy metals. Finally, it was proved that L. nobilis is a suitable organism to be used as a biomonitoring tool for conducting research on heavy metal pollution.
Keywords: OXIDATIVE STRESS; WATER RELATIONS; AIR-POLLUTION; SOIL SAMPLES; CADMIUM; PLANTS; GROWTH; COPPER; LEAD; ACCUMULATION